The Effect of Using Online Mind Mapping as Pre-Writing Strategy on the Quality of Students’ Academic Essays - Dwi Atmoko; Fiqih Kartika Murti; Agung Tyas Subekti (Cakrawala: Jurnal Pendidikan, 2026)
Writing academic essays is an important part of student literacy, but many still struggle to organize ideas in the pre-writing stage. Online mind mapping platforms such as the Coggle application offer interactive visual solutions for writing planning. The purpose of this study was to determine the effect of using online mind mapping as a pre-writing strategy on the quality of students' academic essays. This quasi-experimental study with a non-equivalent control group design involved first-semester undergraduate nursing students at Bhamada Slawi University, divided into experimental (online mind mapping) and control (conventional) classes. Data were obtained through essay assessments on the pretest-posttest and analyzed using paired t-tests and independent t-tests. Both classes experienced significant improvement, but the experimental class showed a higher increase (12.48 points) compared to the control class (11.36 points). The independent t-test showed a significant difference with the experimental class’ posttest average being 3.26 points superior (Sig. = 0.003). Online mind mapping proved to have a significant effect and was more effective than conventional strategies in improving the quality of students' academic essays.